First observation of unlocking the locked mode by electrode biasing on J-TEXT tokamak. (21st December 2020) - Chen, Zhipeng; Wang, Tong; Yu, Qingquan; Hu, Qiming; Li, Da; Yang, Jie; Han, Dongliang; Shen, Chengshuo; Xia, Minghui; Liu, Hai; Wang, Nengchao; Huang, Zhuo; et al.
Abstract: Major disruptions, often caused by locked m / n = 2/1 modes ( m / n is the poloidal/toroidal mode number), are great threat to a tokamak fusion reactor and should be mitigated or avoided. The locked 2/1 modes have been unlocked by electrode biasing (EB) for the first time in J-TEXT tokamak experiments. The application of a sufficiently negative EB voltage in plasma edge region quickly changes the phase and amplitude of the locked 2/1 mode and drives the mode to rotate in about 10–30 ms. For a larger EB current or a smaller locked mode amplitude, the mode is more easily to be unlocked, revealing a new method for mode unlocking and avoiding plasma disruptions.